ONA TILI O‘QITISH METODIKASI FANINI O‘QITISHDA TALABALARNING KREATIV QOBILIYATINI RIVOJLANTIRISH - Farxodova Dilnoza Qudrat qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
the article presents methodological recommendations aimed at developing students' creative thinking, independent analysis and the skills of applying new pedagogical approaches through the discipline of native language teaching methodology. Modern pedagogical technologies and innovative methods for developing creative abilities for teachers and pedagogy students are analyzed. The article shows how the use of creative approaches in teaching native language methodology helps to improve the learning process and helps students freely express their thoughts, analyze and make innovative pedagogical decisions. The article also provides practical examples and recommendations for the development of creative thinking.